Pemetaan Demografi Data Penerimaan Mahasiswa Baru Menggunakan Business Intelligence - Amin, Musa (Jurnal Tika, 2024)
Promoting higher education institutions is a crucial element in increasing the number of new student enrollments. However, these promotional activities often lack a foundation in relevant data. This research aims to elucidate the demographics, study programs, and preferred admission pathways through the application of business intelligence (BI) on the data of new student admissions at IAIN Pontianak. By analyzing data using business intelligence software, the results encompass information on the demographic characteristics of applicants, their school and regional origins, and the admission pathways. Prospective new students are predominantly female, aged 18-20 years, mainly hailing from the city of Pontianak, Kubu Raya Regency, and Mempawah Regency. Lokal 2 and UM-PTKIN admission pathways are the most sought after, with the Sharia Business Management program being the favorite. It was found that BI is effective in analyzing new student admission data, providing a foundation for improving higher education promotion strategies, and the analysis results can be accessed through a dashboard. This research concludes that BI is effective in analyzing the demographic characteristics of new student applicants, enabling institutions to better direct promotion strategies. The Metabase software meets the BI needs of higher education, providing efficient information that can be used for evaluation and planning future promotion strategies.